2007
DOI: 10.1258/095646207782212216
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy in pregnancy

Abstract: Successful interventions to prevent congenital HIV require adherence to highly active antiretroviral therapy (HAART) in pregnancy from mothers and agreement with other interventions including mode of delivery and infant testing. We sought to audit adherence support offered antenatally, adherence with HAART, recommendations for delivery and infant testing in women receiving HIV care at our unit and delivering a child in 2004 and 2005. Of the 32 women identified, an adherence discussion was conducted when commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Untreated depression during pregnancy is also associated with nonadherence to HIV treatment regimens and treatment of depression may improve medication adherence [30]. As poor adherence with antiretroviral drugs during pregnancy may predict nonattendance at infant followup [31], identifying women who are having trouble taking their medication is important.…”
Section: Medication Adherence In Pregnancymentioning
confidence: 99%
“…Untreated depression during pregnancy is also associated with nonadherence to HIV treatment regimens and treatment of depression may improve medication adherence [30]. As poor adherence with antiretroviral drugs during pregnancy may predict nonattendance at infant followup [31], identifying women who are having trouble taking their medication is important.…”
Section: Medication Adherence In Pregnancymentioning
confidence: 99%
“…During pregnancy, a compromised virological response to cART also increases risk of mother-to-child transmission (MTCT) of HIV [ 10 , 11 ], including of drug resistant virus [ 12 ]. Lower levels of adherence to ART during pregnancy have elsewhere been associated with use of illicit drugs, alcohol and tobacco [ 13 15 ], although not consistently [ 16 , 17 ], possibly because of the importance of context-specific factors, particularly availability of harm reduction services [ 18 ]. Access to opioid substitution therapy in Ukraine is poor, with only 6,632 of an estimated 250,000 people injecting opiates receiving methadone or buprenorphine by the end of 2011 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 In another cohort of 32 women, compliance with antenatal clinic and therapy guidelines ranged between 77% and 87% (in our study, 85% of the women were compliant with treatment), and participation in initial postnatal tests was documented in 61% of cases (in our study, 90.8% of the children had at least one test, and 75.8% of the children had a complete diagnosis). 29 In summary, our audit found that the current recommendations were followed in two thirds of the recorded deliveries, as patients delivered at term with an undetectable viral load of an uninfected newborn. Among these, half were vaginal deliveries, and 67% had ruptured membranes for <4 hours and required no instrumental delivery.…”
Section: Audit About Hiv Management Of Pregnancy 1885mentioning
confidence: 78%
“…[24][25][26][27][28][29] Earlier audits focused on compliance with HIV testing and often used surveys to that effect. Our audit focused on therapeutic management, and our results are comparable, to some extent, to what has been observed by other authors.…”
Section: Audit About Hiv Management Of Pregnancy 1885mentioning
confidence: 99%